Preparation and preliminary pharmacokinetics study of GNA-loaded zein nanoparticles. (29th August 2019) - Cheng, Weiye; Wang, Beilei; Zhang, Caiyun; Dong, Qiannian; Qian, Jiajia; Zha, Liqiong; Chen, Weidong; Hong, Lufeng
Abstract: Objectives: Gambogenic acid (GNA), one of the main active ingredients isolated from Garcinia cambogia, has shown diverse antitumour activities. However, short biological half-life and low oral bioavailability severely limit its clinical application. Here, we developed GNA-loaded zein nanoparticles (GNA-ZN-NPs) based on phospholipid complex and zein nanoparticles to prolong the circulation time and enhance oral bioavailability of GNA. Methods: The physicochemical properties of GNA-ZN-NP were characterized in details. The in vitro release profile, in vivo pharmacokinetic experiments and tissue distribution of GNA-ZN-NPs were also evaluated. Key findings: The particle size, PDI and encapsulation efficiency of GNA-ZN-NPs were 102.90 nm, 0.027 and 76.35 ± 0.64%, respectively. The results of SEM, FTIR, DSC and XRD demonstrated that GNA-ZN-NPs were prepared successfully. The in vitro dissolution of GNA-ZN-NPs exhibited controlled release compared with raw GNA solution. The pharmacokinetic study showed that the AUC of GNA-ZN-NPs was significantly increased, and the t1/2 and MRT values of GNA-ZN-NPs were 3.21-fold and 2.19-fold higher than that of GNA solution. Tissue distribution results illustrated that GNA-ZN-NPs showed hepatic-targeting properties. Conclusion: GNA-ZN-NPs significantly enhanced the oral bioavailability and prolonged half-life of GNA, providing a promising oral drug delivery system to improve in vivo pharmacokinetic behaviour of GNA.